Editorial Cartoons and Propaganda Posters of the Union of South Africa’s pro-war press during the First World War; 1914-1918 - Conradie, J. W. (Tiaan) (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.